PEMBUATAN SEL FOTOVOLTAIK PASANGAN CuO/Cu DAN CuO/STAINLESS STEEL DALAM BENTUK TUNGGAL DAN SERABUT MELALUI METODA PERENDAMAN DENGAN NaOH - Tetra, Olly Norita (Jurnal Ilmu Fisika, 2011)
The research about Photovoltaic cell of CuO/Cu and CuO/Stainless steel in single and fiber made by NaOH submersion method by using KCl electrolyte has been done. In this research, the KCl solution is used with different concentrations. The measurement of intensity and voltage is done before and after the Photovoltage cell is radiated by the sun light for approximately 5 minutes. The optimum concentration obtained is 0,3 M. The highest value for intensity and voltage is obtained on fiber CuO/Cu electrodes with the values are 0,364 mA and 0,170 V, measured at 11.00 – 12.00 in the noon. The length time of submersion of Cu electrode with NaOH to is affecting the intensity and voltage of CuO production, submerging in relatively optimal in 24 hour. The Photovoltaic cell can be used with or without the sun light, with the voltage being produced is 0,109 mA for fiber CuO/Cu electrodes. CuO/Cu electrodes and Stainless steel CuO/Cu electrodes can be used on Photovoltaic cell.